1995
DOI: 10.1103/revmodphys.67.457
|View full text |Cite
|
Sign up to set email alerts
|

The appearance and disappearance of the 17-keV neutrino

Abstract: It is a fact of life in empirical science that experiments often give discordant results. This is nowhere better illustrated than in the recent history of experiments concerning the existence of a heavy, 17-keV neutrino. The 17-keV neutrino was first "discovered" by Simpson in 1985. The initial replications of the experiment all gave negative results, and suggestions were made that attempted to explain Simpson's result using accepted physics, without the need for a heavy neutrino. Subsequent positive results b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The different involved m i produce kinks in the Kurie-plot where the size of the kinks is a measure for the corresponding mixing angle. This was discussed in connection with the now ruled out 17 keV -neutrino [19,20]. The search for an eV-neutrino near the endpoint region is complicated due to several effects [21,22].…”
Section: Beta Decaymentioning
confidence: 97%
See 1 more Smart Citation
“…The different involved m i produce kinks in the Kurie-plot where the size of the kinks is a measure for the corresponding mixing angle. This was discussed in connection with the now ruled out 17 keV -neutrino [19,20]. The search for an eV-neutrino near the endpoint region is complicated due to several effects [21,22].…”
Section: Beta Decaymentioning
confidence: 97%
“…In SO(10) B-L is not necessarily conserved opening the chance for Majorana mass terms as well. The breaking of SO(10) allows different schemes like SO(10) → SU(5) → SU(3) ⊗ SU(2) ⊗ U(1) (19) or into a left-right symmetric version after the Pati-Salam model [16]…”
Section: Neutrino Masses In Grand Unified Theoriesmentioning
confidence: 99%
“…This has been confirmed experimentally in [106] (see § 6.5). It can also be shown that (44) can be approximated by the expression…”
Section: The 187 Re Beta Decay Spectrummentioning
confidence: 99%
“…Their detailed account can be found in refs. [200], [201]. "The rise and fall of the 17 keV neutrino" was also briefly described in ref.…”
Section: Previous Experimentsmentioning
confidence: 98%